Mathematical Induction (1) - Section2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 13

1

Mathematical
induction
 Suppose that we have an infinite ladder, as shown in Figure 1,
and we want to know whether we can reach every step on
this ladder. We know two things: 2
1. We can reach the first rung of the ladder.
2. If we can reach a particular rung of the ladder, then we can
reach the next rung.
 We conclude that we can reach every rung.
By (1), we know that we can reach the first rung of the ladder.
Moreover, because we can reach the first rung, by (2), we can
also reach the second rung; it is the next rung after the first rung. P(i)
Applying (2) again, because we can reach the second rung, we
can also reach the third rung. Continuing in this way, we can ∀k(P(k)→P(k+1))
show that we can reach the fourth rung, the fifth rung, and so
on……
∀n P (n)
 In the same manner to prove that P(n) is true ∀n ≥ i ; n is an
integer, where P(n) is a propositional function, we complete
two steps
1. Basis step
We verify that P(i) is true.
2. Inductive step
We show that the conditional statement P(k) → P(k + 1) is true for
all positive integers k.
Template for Proofs by Mathematical Induction 3

 Express the statement that is to be proved in the form “for all n ≥ i,


P(n)” for a fixed integer i.
 Basis Step:
show that P(i) is true, taking care that the correct value of (i) is used.
This completes the first part of the proof.
 Inductive Step:
1.assume that P(k) is true for an arbitrary fixed integer k ≥ i.(inductive
hypothesis)
2. State the statement P(k + 1) which we need to be prove.
 Prove the statement P(k + 1) making use the assumption P(k).
5. Prove that 4
12 + 32 + 52 +· · · +(2𝑛 + 1)2 = (𝑛 + 1)(2𝑛 + 1)(2𝑛 + 3)/3
whenever 𝑛 is a nonnegative integer.
𝑛+1 2𝑛+1 2𝑛+3
 Let 𝑃 𝑛 : 12 + 32 + 52 +· · · +(2𝑛 + 1)2 = ;𝑛 ≥ 0
3
0+1 2 ∙ 0+1 2 ∙ 0+3
 Basis step: 𝑃 0 : 12 =
3

The L.H.S=R.H.S=1 ∴ 𝑃 0 is true.


 Inductive step:
1.assume that 𝑃 𝑘 Is true.
𝑘 + 1 2𝑘 + 1 2𝑘 + 3
𝑃 𝑘 : 12 + 32 + 52 +· · · +(2𝑘 + 1)2 = (∗)
3
2. we need to prove 𝑃 𝑘 + 1 is true?
𝑘 + 2 2𝑘 + 3 2𝑘 + 5
𝑃 𝑘+1 : 12 + 32 + 52 +· · · +(2(𝑘 + 1) + 1)2 =
3
 From the L.H.S of 𝑃 𝑘 + 1 :
5
12 + 32 + 52 +· · · +(2𝑘 + 3)2 = 12 + 32 + 52 +· · · +(2𝑘 + 1)2 +(2𝑘 + 3)2
Using (∗) we get
𝑘 + 1 2𝑘 + 1 2𝑘 + 3
12 + 32 + 52 +· · · +(2𝑘 + 3)2 = + (2𝑘 + 3)2
3

2𝑘 + 3 2𝑘 + 3
= 𝑘 + 1 2𝑘 + 1 + 3 2𝑘 + 3 = 2𝑘 2 + 3𝑘 + 1 + 6𝑘 + 9
3 3

2𝑘 + 3 2
2𝑘 + 3
= 2𝑘 + 9𝑘 + 10 = (2𝑘 + 5)(𝑘 + 2)
3 3
Equal the R.H.S of 𝑃 𝑘 + 1 .
Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for all
nonnegative integer 𝑛.
1 1 1 1
10. a) Find a formula for 1 · 2 + 2 · 3 + 3 · 4 +· · · + 𝑛(𝑛 + 1)
6
b) For which nonnegative integers 𝑛 the formula you
conjectured in part (a) is valid? Prove your answer.
 a)
1 1
=
1 · 2 2
1 1 4 2
+ = =
1 · 2 2 · 3 6 3
1 1 1 9 3
+ + = =
1 · 2 2 · 3 3 · 4 12 4
Therefore we can note that the formula is
1 1 1 1 𝑛
+ + +· · · + =
1 · 2 2 · 3 3 · 4 𝑛(𝑛 + 1) 𝑛 + 1
 b) the formula valid for any positive integer.
1 1 1 1 𝑛
 Let 𝑃 𝑛 : + + +· ··+ = ;𝑛 ≥ 1
1·2 2·3 3·4 𝑛(𝑛 + 1) 𝑛+1
1 1
 Basis step: 𝑃 1 : =
1·2 1+1
1
The L.H.S=R.H.S= ∴ 𝑃 1 is true.
2
 Inductive step:
1.assume that 𝑃 𝑘 Is true.
𝑃 𝑘 :
1
+
1
+
1
+· · · +
1
=
𝑘
(∗)
7
1 · 2 2 · 3 3 · 4 𝑘(𝑘 + 1) 𝑘 + 1
2. we need to prove 𝑃 𝑘 + 1 is true?
1 1 1 1 1 𝑘+1
𝑃 𝑘+1 : + + +· · · + + =
1 · 2 2 · 3 3 · 4 𝑘(𝑘 + 1) (𝑘 + 1)(𝑘 + 2) 𝑘 + 2
 From the L.H.S of 𝑃 𝑘 + 1 :
1 1 1 1 1
+ + +· · · + +
1 · 2 2 · 3 3 · 4 𝑘(𝑘 + 1) (𝑘 + 1)(𝑘 + 2)
Using (∗) we get
1 1 1 1 1
+ + +· · · + +
1 · 2 2 · 3 3 · 4 𝑘(𝑘 + 1) (𝑘 + 1)(𝑘 + 2)

𝑘 1 𝑘 𝑘+2 +1 𝑘 2 + 2𝑘 + 1 𝑘+1
= + = = =
𝑘 + 1 (𝑘 + 1)(𝑘 + 2) (𝑘 + 1)(𝑘 + 2) (𝑘 + 1)(𝑘 + 2) 𝑘 + 2

Equal the R.H.S of 𝑃 𝑘 + 1 .


Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for any
positive integer 𝑛.
1 𝑗 2𝑛+1 + −1 𝑛
12. Prove that 𝑛
𝑗=0(− 2) = whenever n is a 8
3·2𝑛
nonnegative integer.
1 𝑗 2𝑛+1 + −1 𝑛
 Let 𝑃 𝑛 : 𝑛
𝑗=0 (− ) = ;𝑛 ≥ 0
2 3· 2𝑛
1 20+1 + −1 0
 Basis step: 𝑃 0 : (− )0 =
2 3· 20

The L.H.S=R.H.S=1 ∴ 𝑃 0 is true.


 Inductive step:
1.assume that 𝑃 𝑘 Is true.
𝑘
1 𝑗 2𝑘+1 + −1 𝑘
𝑃 𝑘 : (− ) = (∗)
2 3 · 2𝑘
𝑗=0

2. we need to prove 𝑃 𝑘 + 1 is true?


𝑘+1
1 𝑗 2𝑘+2 + −1 𝑘+1
𝑃 𝑘+1 : (− ) =
2 3 · 2𝑘+1
𝑗=0
 From the L.H.S of 𝑃 𝑘 + 1 :
𝑘+1
1 𝑗
𝑘
1 𝑗 1 𝑘+1 9
(− ) = (− ) + (− )
2 2 2
𝑗=0 𝑗=0
Using (∗) we get
𝑘+1
1 𝑗 2𝑘+1 + −1 𝑘 1 𝑘+1 2𝑘+1 + −1 𝑘 −1 𝑘+1
(− ) = + (− ) = +
2 3 · 2𝑘 2 3 · 2𝑘 2𝑘+1
𝑗=0
2 2𝑘+1 + −1 𝑘 + 3 −1 𝑘+1
=
3 · 2𝑘+1

2𝑘+2 + 2 −1 𝑘 − 3 −1 𝑘
=
3 · 2𝑘+1

2𝑘+2 − −1 𝑘
2𝑘+2 + −1 𝑘+1
= =
3 · 2𝑘+1 3 · 2𝑘+1

Equal the R.H.S of 𝑃 𝑘 + 1 .


Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for all
nonnegative integer 𝑛.
34-Prove that 6 divides 𝑛3 − 𝑛 whenever n is a nonnegative 10
integer.
 Let 𝑃 𝑛 : 6 divides 𝑛3 − 𝑛 ; 𝑛 ≥ 0
 Basis step: 𝑃 0 : 6 divides 03 − 0
03 − 0 = 0 , 0/6 = 0 ∴ 6 divides 03 − 0
∴ 𝑃 0 is true.
 Inductive step:
1.assume that 𝑃 𝑘 Is true. 𝑃 𝑘 : 6 divides 𝑘 3 − 𝑘 (∗)
2. we need to prove 𝑃 𝑘 + 1 is true? 𝑃 𝑘 + 1 : 6 divides (𝑘 + 1)3 −(𝑘 + 1)
 (𝑘 + 1)3 − 𝑘 + 1 = 𝑘 3 + 3𝑘 2 + 3𝑘 + 1 − 𝑘 − 1 = 𝑘 3 − 𝑘 + 3(𝑘 2 + 𝑘)
From (∗) we know that 6 divides 𝑘 3 − 𝑘. Also we note that 𝑘 2 + 𝑘 is an
even integer, since 𝑘 2 + 𝑘 = 𝑘(𝑘 + 1) is a product of Two consecutive
integers which one of them must be even. So 𝑘 2 + 𝑘 = 2 𝑚 ; 𝑚 is an
integer, thus 6 divides 3 𝑘 2 + 𝑘 . Therefore 6 divides (𝑘 + 1)3 −(𝑘 + 1).
Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for all
nonnegative integer 𝑛.
1 1 1 1
19. Let P(n) be the statement that 1 + +9 + · · · + 𝑛2 < 2−
4 𝑛 11
,where n is an integer greater than 1.

1 1 1 1
 Let 𝑃 𝑛 : 1 + + + · · · + <2− ;𝑛 > 1
4 9 𝑛2 𝑛
1 1
 Basis step: 𝑃 2 : 1 + < 2 −
4 2
1 1
The 𝐿. 𝐻. 𝑆 = 1 < 𝑅. 𝐻. 𝑆 = 1 ∴ 𝑃 2 is true.
4 2

 Inductive step:
1.assume that 𝑃 𝑘 Is true.
1 1 1 1
𝑃 𝑘 : 1 + + + · · · + 2 < 2 − (∗)
4 9 𝑘 𝑘
2. we need to prove 𝑃 𝑘 + 1 is true?
1 1 1 1
𝑃 𝑘 + 1 :1 + + +· · · + <2−
4 9 (𝑘 + 1)2 𝑘+1
 From the L.H.S of 𝑃 𝑘 + 1 :
1 1 1 1 1 1 1 12
1+ + +···+ 2
= 1+ + +···+ 2+
4 9 (𝑘 + 1) 4 9 𝑘 (𝑘 + 1)2
Using (∗) we get
1 1 1 1 1 1 1
1+ + +···+ <2− + =2−( − )
4 9 (𝑘 + 1)2 𝑘 𝑘+1 2 𝑘 𝑘+1 2
To prove 𝑃 𝑘 + 1 is true we will show that
1 1 1
2− − < 2 −
𝑘 𝑘+1 2 𝑘+1
1 1 1
To prove this inequality we just need to show that (− 𝑘

𝑘+1 2
+
𝑘+1
< 0)
1 1 1 1 1 1 −(𝑘 + 1)2 + 1 + 𝑘(𝑘 + 1)
− − 2
+ =− + 2
+ = 2
𝑘 𝑘+1 𝑘+1 𝑘 𝑘+1 𝑘+1 𝑘 𝑘+1

−𝑘 2 − 2𝑘 − 1 + 1 + 𝑘 2 + 𝑘 −𝑘 −1
= = = <0
𝑘 𝑘+1 2 𝑘 𝑘+1 2 𝑘+1 2

Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for all


nonnegative integer 𝑛.
21. Prove that 2𝑛 > 𝑛2 if 𝑛 is an integer greater than 4. 13
 Let 𝑃 𝑛 : 2𝑛 > 𝑛2 ; 𝑛 > 4
 Basis step: 𝑃 5 : 25 > 52
The 𝐿. 𝐻. 𝑆 = 25 = 32 > 𝑅. 𝐻. 𝑆 = 52 = 25 ∴ 𝑃 5 is true.
 Inductive step:
1.assume that 𝑃 𝑘 Is true. 𝑃 𝑘 : 2𝑘 > 𝑘 2 (∗)
2. we need to prove 𝑃 𝑘 + 1 is true? 𝑃 𝑘 + 1 : 2𝑘+1 > (𝑘 + 1)2
From (∗) we know that
2𝑘 > 𝑘 2 ∗2
2 ∙ 2𝑘 > 2 ∙ 𝑘 2
2𝑘+1 > 2 ∙ 𝑘 2 = 𝑘 2 + 𝑘 2 = 𝑘 2 + 𝑘 + 𝑘 + 𝑘 + ⋯ + 𝑘 > 𝑘 2 + 2𝑘 + 1 > (𝑘 + 1)2
(𝑘 − 𝑡𝑖𝑚𝑒𝑠)
Therefore 𝑃 𝑘 + 1 is true, by mathematical induction, 𝑃(𝑛) is true for all
integer 𝑛 greater than 4.

You might also like